Empreendimentos econômicos e política ambiental na Amazônia: um estudo sobre os programas ambientais e a educação ambiental no contexto da Mineração Alcoa no município de Juruti no estado do Pará - VELLOSO, Leônidas Pompeu Leão (Universidade Federal do Pará, 2018)
This work aims to study the relationships that have to build from the installation of Bauxite Mine Extraction Company by Alcoa in the municipality of Juruti. The objective is to study the social and environmental impact that the installation of mining is causing and from a critical and emancipatory understand how the state, society and business are related and what interests are served. The theoretical construction of this work takes as a foundation for discussion of environmental complexity, environmental education in environmental management, development processes in Amazonia, democracy and modes of production, together with these elements that the discussion of the logic of capital. The mining company has to change production methods and habits of a significant part of local people to understand that the methodology was the lifting of quantitative and qualitative data, which were constructed from interviews with local actors, information collected through institutions working with statistical data and literature surveys for the construction of the theoretical discussion together with the reports that were presented in the media. The analysis of the indicators presented by the company and its program of environmental education were two important instruments for the analysis of work, because it is possible to see how weak the process of building a real alternative to improving the lives of people where the lack of governance and straightforward way to ensure governance dictate orders. The completion of the work shows that the social and environmental impact caused by the company significantly changed the lives of local people, their habits, their customs, their mode of production. Promoted the increase of diseases and injuries caused by poisonous animals, caused the swelling of the headquarters of the city and that so far the measures the company took in March of mitigation are small impacts, such as improving the selective collection of solid waste.